ANALISIS KEPEMIMPINAN WIDYA KANDI SUSANTI SEBAGAI CALON PETAHANA YANG GAGAL PADA PILKADA DI KABUPATEN KENDAL TAHUN 2015 - Denis Sitio; Muhammad Adnan (Journal of Politic and Government Studies, 2018)
The leadership of incumbent candidates is one of the important points in determining the acquisition of vote results in the Regional Head Election. At the end of their tenure, a public leader becomes the object of evaluation for the people who have implications for a conclusion and a political attitude, that is "continue" or "stop". The phenomenon of the defeated incumbent candidate Widya Kandi Susanti – Mohamad Hilmi in the election of Kendal District in 2015 which is only able to obtain 37.77% of the vote, attracted researchers to 2 scrutinize and present the leadership practices of Widya Kandi Susanti during her five years leadership when she served as Regent Kendal Regency for the period of 2010-2015. The theory which is used focuses on the aspects of leadership with reference to the managerial competence of a public leader.The method which is used with the type of qualitative research through descriptive analysis approach.In this study it was found that the leadership of Widya Kandi Susanti has been well implemented, but the leadership that can be said succeeded is not able to bring the pair of incumbent candidate Widya Kandi Susanti – Mohamad Hilmi in winning in Pilkada Kendal regency in 2015. The failure is caused by the physical construction of road infrastructure which is still very minimal, other than that the negative issues about Widya Kandi Susanti circulating in the same year with the implementation of election is also a factor of her failure in the election in Kendal District in 2015.Keywords: leadership, incumbent candidate, failure